The relationship between game success indicators in the FIFA World Cup - Qatar 2022: An elastic-net regularization approach - Armend Myftiu; Agron Thaqi (IP Iermakov S.S., 2023)
Background and Study Aim. The significance of analyzing statistical indicators is paramount, as they provide valuable insights into the distinguishing performance factors of teams. The purpose of this study: 1)  to identify statistically significant differences between relevant performance factors among winning, drawing, and losing teams in the 2022 Football World Cup in Qatar; 2) explore indicators that are most strongly associated with the game results in this tournament. Material and Methods. A total of 64 matches and 32 participating teams were analyzed. The variables included in the research were: total shots, shots on target, shots off target, effectiveness, passes, passes completed, crosses, crosses against, offsides committed, offsides received, fouls received, ball possession, fouls committed, corners, corners against, yellow cards and red cards. The results are extracted from the official FIFA website. The Analysis of Variance (ANOVA) and the ordinal logistic regression with elastic net were used for data calculation. Results. The results indicate that winning teams have statistically significantly higher mean values of variables related to goals scored: total shots (p < 0.05), shots on target (p < 0.01), and effectiveness (p < 0.01). According to the information-based model selection criteria AIC (Akaike information criterion) and BIC (Bayesian information criterion) effectiveness and shots on target are the most important variables regarding game results. They, along with corners, are best associated with successful teams. In contrast, crosses, ball possession, corners against, and yellow cards are associated with less successful teams. Results suggest that teams with high ball possession and large number of crosses, but fewer shots on target, have weaker results than teams with more shots on target and less ball possession. Conclusions. The study underscores the significance of certain performance indicators, such as total shots, shots on target, and effectiveness, in predicting a team's success. These findings provide valuable insights for coaches and teams to focus on specific aspects of their game to enhance their chances of winning. Additionally, understanding the impact of variables like ball possession, crosses, corners, and yellow cards emphasizes the importance of a well-rounded strategy for achieving success in international football tournaments.